2021
DOI: 10.20960/nh.03383
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between BsmI polymorphism and VDR gene methylation profile, gender, metabolic profile, oxidative stress, and inflammation in adolescents

Abstract: Relationship between BsmI polymorphism and VDR gene methylation profile, gender, metabolic profile, oxidative stress, and inflammation in adolescentsRelación entre polimorfismo BsmI y perfil de metilación del gen VDR, género, perfil metabólico, estrés oxidativo e inflamación en adolescentes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
1
1
0
1
Order By: Relevance
“…As with the TaqI polymorphism, the methylation profile of the VDR gene was not associated with oral mucositis in this study, and the partially methylated profile in the promoter region of the VDR gene was found in all individuals (Table 4). Recently, a study addressing the methylation profile in the promoter region of the VDR gene in adolescents without cancer in the same city where the present study was conducted also found partial methylation, in which the mean ranged from 26% (±12.4%) to 30% (±14.2%) in blood cells (Lacerda de Lucena et al, 2021). In our study, although it did not take a quantitative approach, the analysis of the electrophoresis gels suggests partial methylation of around 50% in oral cells, since the bands of the methylated and unmethylated conditions seem equivalent (Figure 2).…”
Section: Discussionsupporting
confidence: 53%
“…As with the TaqI polymorphism, the methylation profile of the VDR gene was not associated with oral mucositis in this study, and the partially methylated profile in the promoter region of the VDR gene was found in all individuals (Table 4). Recently, a study addressing the methylation profile in the promoter region of the VDR gene in adolescents without cancer in the same city where the present study was conducted also found partial methylation, in which the mean ranged from 26% (±12.4%) to 30% (±14.2%) in blood cells (Lacerda de Lucena et al, 2021). In our study, although it did not take a quantitative approach, the analysis of the electrophoresis gels suggests partial methylation of around 50% in oral cells, since the bands of the methylated and unmethylated conditions seem equivalent (Figure 2).…”
Section: Discussionsupporting
confidence: 53%
“…Notwithstanding, other groups have reported low PTH levels in patients carrying the BB genotype. (24,25) The bb genotype has been found to be associated with a higher frequency of diabetes and inflammation (26,27). For this reason, bb associated with inflammation and diabetes were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Представленные данные получены впервые. В предшествующих работах были предприняты попытки исследовать полиморфизм гена у взрослых с атопическим дерматитом [14], при этом была установлена большая частота встречаемости аллеля G в сайте BsmI гена VDR rs1544410), аллеля С в сайте ApaI (rs7975232) и аллеля T в Анализируя данные содержания 25-OH витамина D, обращает на себя внимание статистически значимое снижение его (Р=0,02) концентрации у детей при гетерозиготном варианте A/G и гомозиготном варианте G/G Fok1 гена VDR (табл. 2).…”
Section:  результаты и обсуждениеunclassified